2000
DOI: 10.1016/s0925-4439(99)00100-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxidative stress based on lipid hydroperoxide, vitamin C and vitamin E during apoptosis and necrosis caused by thioacetamide in rat liver

Abstract: After 12 h of thioacetamide (500 mg/kg body weight) administration to rats, the activity of caspase-3-like protease in the liver increased significantly compared to that in the control group. In plasma, the activity of caspase-3 was barely detectable in the control rat, but had increased significantly after 24 h of drug administration along with a dramatic increase in GOT. These results indicate that thioacetamide causes apoptosis in the liver by activating caspase-3, which is released to plasma by successive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 25 publications
7
56
0
3
Order By: Relevance
“…In the present study, the SOD and CAT activities were significantly decreased after D-Gal administration, while the group of rats administered with ULP did not exhibit impairment of antioxidant enzymes (p50.001; Figure 3a and b). This result is in agreement with a general view that administration of an antioxidant agent can neutralize potentially harmful free radicals in the cells before they can cause lipid or protein oxidation (Sun et al, 2000). Few studies have shown that Phase II enzyme genes, which are also referred to as antioxidant response elements, are triggered by oxidant stress or by mixed reactions from other antioxidant products (Cahyana et al, 1992;Wolf, 2001).…”
supporting
confidence: 90%
“…In the present study, the SOD and CAT activities were significantly decreased after D-Gal administration, while the group of rats administered with ULP did not exhibit impairment of antioxidant enzymes (p50.001; Figure 3a and b). This result is in agreement with a general view that administration of an antioxidant agent can neutralize potentially harmful free radicals in the cells before they can cause lipid or protein oxidation (Sun et al, 2000). Few studies have shown that Phase II enzyme genes, which are also referred to as antioxidant response elements, are triggered by oxidant stress or by mixed reactions from other antioxidant products (Cahyana et al, 1992;Wolf, 2001).…”
supporting
confidence: 90%
“…Schizandrae chinensis, a potent anti-oxidant, lowers ALT levels in patients with chronic viral hepatitis [22] . Administration of glutathione to patients with chronic hepatitis significantly decreases GSH-Px activity of catalase (CAT), and increases superoxide dismutase (SOD) activity [23,24] . N-acetyl-cysteine, sodium selenite and vitamin E have also been studied as supplementation to interferon therapy for patients with chronic HCV infection [25] .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, celecoxib significantly reduced the oxidative stress in the liver during the second phase of CCl 4 intoxication based on hepatic vitamin C level, which was the most sensitive indicator of oxidative stress during hepatitis caused by chemicals such as CCl 4 , 15) thioacetamide, 19) or D-galatosamine. 20) Although an antioxidant such as a-tocopherol inhibited liver necrosis caused by CCl 4 via direct reduction of oxidative stress, 21) a different mechanism should operate in the inhibition of oxidative stress by celecoxib.…”
Section: Discussionmentioning
confidence: 91%